Luidia changi, a new sea star species (Echinodermata: Asteroidea: Luidiidae) from the Yellow Sea, with a review of two related species - Liu, Wei; Liao, Yulin; Li, Xinzheng (Zootaxa, 2006)
In the collections of the Institute of Oceanology, Chinese Academy of Sciences, a new species, Luidia changi sp. nov. was discovered mixed in with two closely allied species, L. quinaria von Martens, 1865 and L. yesoensis Goto, 1914. L. changi is described herein; it differs from the two known species in details of abactinal plates, abactinal spinelets, body proportions, and in geographic distributions of the three species.